Neglected Canadian Orchestral Music - Elliott, Robin (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2013)
This article examines neglected orchestral works by six Canadian composers: Rodolphe Mathieu, Colin McPhee, John Weinzweig, Harry Somers, Istvan Anhalt, and R. Murray Schafer. Despite the considerable professional accomplishments and career achievements of these composers, each has at least one orchestral work in his catalogue that failed to make a good impression with the musical public or has never been heard in live performance. The article attempts to find why these compositions did not win a place in the repertoire and also considers how these works illustrate broader issues relating to the Canadian orchestral repertoire.